Professional training for students of teaching degree programs through participation in work environments - Mastache, Anahí (Universidad Nacional del Litoral, 2021)
The Education Sciences Degree Program at Universidad de Buenos Aires, Argentina, provides — at various stages of the program —  curricular subjects that must be developed in professional performance fields. For years now, we have been generating education proposals based on internship programs from our dual role of teachers and members of the pedagogical team of the Subsecretariat of Academic Degree Planning, Teacher Training and Educational Innovation (formerly of Secretariat of Educational Quality) of the Faculty of Engineering, Universidad de Buenos Aires (FIUBA). In this subject, students get involved in some tasks developed by the pedagogical team, namely: analysis of course programs and suggestions for improvement to teachers; survey of responses collected from different universities around the world about engineering teaching in general and about specific issues of interest; observation, analysis, and suggestions for those in charge of different activities (training courses for teachers, activities for high school students, among others). This paper is intended to give an account of the dynamics of the course development, interventions of tutors, and the identification of educational impacts by means of various indicators such as written works and demonstrations in knowledge exchange stages.